The Effect of Organizational Politics on Budgetary Participation with Procedural Fairness as a Mediation - Gabriela Andre Agung; SeTin SeTin (Journal of Economics, Business, and Accountancy Ventura, 2021)
Organizational politics and budgeting are the phenomena that exist in every organization. This study aims to examine the effect of organizational politics on budgetary participation through procedural fairness. Organizational politics refers to three dimensions, namely general political behavior, politics of going along to get ahead, and politics of pay and promotion policies. Data were collected through a questionnaire survey to 128 managers in the retail sector of the modern supermarket in Bandung, West Java, Indonesia. The data was processed using the structural equation model and Sobel test. This study shows that, firstly, general political behavior, politics of going along to get ahead, pay and promotion policies have a negative effect on procedural fairness. Second, procedural fairness has a positive effect on budgetary participation. Third, procedural fairness mediates the relationship between each organizational political dimension and budgetary participation. This study supports the theory of organizational politics and procedural fairness and has the implications for budgeting practices, namely that it is important to consider employee's perceptions of organizational politics because it has an impact on reducing the sense of fairness and eventually on budgetary participation.